Computational Intelligence Paradigms in Advanced Pattern Classification - Ogiela, Marek R.; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This monograph presents selected areas of application of pattern recognition and classification approaches including handwriting recognition, medical image analysis and interpretation, development of cognitive systems for image computer understanding, moving object detection, advanced image filtration and intelligent multi-object labelling and classification. It is directed to the scientists, application engineers, professors, professors and students will find this book useful.
Recent Advances in Pattern Classification -- Neural Networks for Handwriting Recognition -- Moving object detection from mobile platforms using stereo data registration -- Pattern Classifications in Cognitive Informatics -- Optimal Differential Filter on Hexagonal Lattice -- Graph image language techniques supporting advanced classification and cognitive interpretation of CT coronary vessel visualizations -- A graph matching approach to symmetry detection and analysis -- Pattern classification methods for analysis and visualization of brain perfusion CT maps -- Inference of co-occurring classes: Multi-class and multi-label classification.
Keywords: Engineering; Artificial intelligence; Optical pattern recognition; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Pattern Recognition